2011
DOI: 10.1007/s11195-011-9227-3
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Opinions of Turkish University Students About Contraceptive Methods and Emergency Contraception

Abstract: This study was carried out to determine the knowledge and opinions of university students about contraceptive methods and emergency contraception (EC). The study comprised 1,689 students who volunteered to participate in the study and were selected from among students studying in two different universities in the 2007-2008 semester. Data were collected on a form that was developed by researchers. The chi-square test was used for the statistical analysis of the data. Oral contraceptive pills (93%), condoms (91.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 21 publications
2
13
0
3
Order By: Relevance
“…In terms of sexual experience background, we found that the rate of coital experience was 64.9% for men and 53.3% for women. Past studies with Turkish college students established similar rates for men (e.g., Aras, Orcin, Ozan, & Semin, 2007;Boratav & Çavdar, 2012) but lower rates for women (e.g., Aras et al, 2007;Golbasi, Erenel, & Tugut, 2012). The higher number of sexually experienced women in the present sample may be related to a liberalization of sexual behaviors and attitudes among Turkish college students in recent years (see Gelbal et al, 2008).…”
Section: Discussionsupporting
confidence: 51%
“…In terms of sexual experience background, we found that the rate of coital experience was 64.9% for men and 53.3% for women. Past studies with Turkish college students established similar rates for men (e.g., Aras, Orcin, Ozan, & Semin, 2007;Boratav & Çavdar, 2012) but lower rates for women (e.g., Aras et al, 2007;Golbasi, Erenel, & Tugut, 2012). The higher number of sexually experienced women in the present sample may be related to a liberalization of sexual behaviors and attitudes among Turkish college students in recent years (see Gelbal et al, 2008).…”
Section: Discussionsupporting
confidence: 51%
“…Main sources of information included family, neighbours, friends, media, healthcare professionals, books and television [32,33,49]. Qualitative evidence suggests that information on family planning was predominantly obtained from family, neighbours and friends [80-83, 86, 89, 90].…”
Section: Theme 1: Insufficient Knowledge and Misconceptions About Conmentioning
confidence: 99%
“…On the other hand, many women expressed negative attitudes towards family planning for limiting the number of children [26,32,39,86,88,89]. Some women believed that it would be easier to raise and care for their children if they were closely spaced.…”
Section: Theme 5: Attitudes Towards Family Planningmentioning
confidence: 99%
“…Studies in Africa, have generally documented low knowledge and awareness levels of effective contraceptive use amongst higher educational students [10]. Several factors including age, culture, ethnicity, religion, poor access to contraceptive services, peer pressure and lack of partner support were identified as contributing to the non-utilisation of contraceptives in tertiary institutions [11]. In a study amongst 15 to 24 year old South African women, it was estimated that only 52.2% of sexually experienced women are using contraceptives [12].…”
Section: Introductionmentioning
confidence: 99%